A study on low back pain among ambulance workers in the state of Kelantan - Tuan Lonik, Engku Ariff (2015)
INTRODUCTION: Low back pain (LBP) is one of the major musculoskeletal disorders (MSDs) faced by health care workers worldwide, resulting in serious social and economic impact. Among them, the ambulance workers are particularly at risk of developing LBP, due to their nature of work. However, only a few research were conducted in the past to study the problem of LBP among the ambulance workers. OBJECTIVES: The purposes of this study are to describe the prevalence and associated factors of LBP among ambulance workers in the state of Kelantan. METHODOLOGY: A self-administered questionnaire regarding LBP was distributed to all ambulance workers working in a university hospital (Universiti Sains Malaysia) and nine (9) government hospitals in the state of Kelantan. The questionnaire adopted and integrated three existing questionnaires, which are the Nordic Musculoskeletal Questionnaire (NMQ), Low Back Pain Risk Factor Questionnaire (RFQ) and 21-items Depression, Anxiety and Stress Score (DASS-21). A total of 143 completed questionnaires fulfilled the inclusion and exclusion criteria were included in the study. Statistical analysis was carried out with Chi-square test, Fisher’s Exact test and Mann-Whitney test. RESULTS: The lifetime prevalence of LBP among ambulance workers in the state of Kelantan is 65.0% (Confidence Interval, CI 57.1 – 72.9). LBP was associated with male gender (p value: 0.035), smoking (p value: 0.001) and involvement in out-door activities (p value: 0.001). Carrying load with one hand is the only work-related ergonomic hazard associated with LBP (p value: 0.024). The negative psychological affects studied; depression, anxiety and stress are not associated with LBP (p value > 0.05). CONCLUSIONS: This study confirmed the high prevalence of LBP among the ambulance workers. It also identified several factors that are associated with the development of LBP among this particular group of health workers. However, larger studies need to be carried out to properly understand the magnitude and impacts of LBP and other MSD among this profession.